Interactive Aqueous Ink from Core‐Shell Liquid Metal and PEDOT:PSS. Issue 2 (6th October 2022) - Peng, Hao; Peng, Yan; Lan, Jingyun; Zhou, Jiancheng; Zhang, Jiuyang
Abstract: Liquid metals (LMs) and conjugated polymers are both critically important materials in modern technologies including soft robotics, printable circuits, and stretchable electronics. Although broadly applied, the joint use of LMs and conjugated polymers are rarely explored due to the notoriously interfacial challenges of the high surface tension of LMs and the unfavorable rigid backbones of conjugated polymer chains. This work successfully introduced conjugated polymers (poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate, (PEDOT:PSS)) into the system of liquid metals to provide a highly stable, aqueous, and electrically conductive ink (LM‐PEDOT:PSS inks, LMPInks) for flexible electronics. The PSS segments act as a strong ionic bridge to effectively stabilize core‐shell structure of the PEDOT and LMs in the homogenous ink. Different from previous insulated LM‐inks, LMPInk is aqueous and more importantly, electrically conductive without posttreatments due to the intrinsically conductive PEDOT:PSS. Interestingly, with low content of LM particles (<2 wt%), the printed circuits inherit the valuable transparency of PEDOT:PSS (transmission >92% in visible region), which has never been observed in LM‐based organic systems. Furthermore, such LMPInks show distinguished electrical robustness, which can automatically recover their initial electrical conductivity even after severe physical damage. With the above phenomenal advantages, various flexible circuits on different substrates are successfully provided. Abstract : This work is the first time to stabilize the liquid metal (LM) by conjugated polymers (PEDOT:PSS), which forms an interactive aqueous ink (LMPInk) with core‐shell structural LM@PEDOT:PSS. Different from insulated LM‐inks, such LMPInks have initial electrical conductivity and inherit the valuable transparency of PEDOT:PSS. Compared with PEDOT:PSS, printed LMPInks can autonomously and instantaneously restore electrical function after severely physical damage.